Qaraqalpaq xalıq jańıltpashları tilinde ornitonimlerdiń qollanılıwı - Allamuratova, D.X (SCIENCE and SOCIETY, 2025)
The article examines the lexical and stylistic features and distinctive features of ornithonyms in the language of Karakalpak folk tongue twisters. In it, through the peculiarity of the bird, the disclosure of a sign characteristic of an entire nation, the hunting of birds and the consumption of their meat, the creation of sacred bird names and ornithonyms in a symbolic image are discussed. In addition to the ornithonymic function, the use of bird names in services, the assignment of professional names of the Karakalpak people related to birds are scientifically analyzed based on relevant examples.